Quality parameters of spiny lobster (Panulirus interruptus) tails as affected by short-term emersion at two different air temperatures - E Márquez-Ríos; S Gómez-Jiménez; VM Ocaño-Higuera; FJ Castillo-Yáñez; R Pacheco-Aguilar (Ciencias Marinas, 2007)
The spiny lobster, Panulirus interruptus, is a valuable crustacean and most of its production is marketed live. In the northern fisheries of Baja California, Mexico, the animals are exposed to short-term emersion at different air temperatures during the live marketing procedures. This work evaluates the effect of short-term emersion (up to 10 h) at two air temperatures (7ºC and 20ºC) and of a 2-h recovery period on ATP, its related metabolites and some muscle quality parameters. Survival was 100% after all emersion times. No significant differences were found either in the adenylic energetic charge or in the levels of ATP and its related metabolites. The highest concentrations were found for AMP, IMP and INO, while ATP had the lowest levels. Muscle quality parameters such as water holding capacity and shear force remained similar to the control values. Although pH decreased slightly with emersion, it was very close to the control values after the 2-h recovery period. The overall results suggest that P. interruptus may perform physiological compensatory work after 10 h emersion even at 20ºC without significantly affecting the muscle quality.